THE ACCOUSTIC OBSERVATION AND THE EXPLOITATION OF THE PURSE SEINE FISHERY IN THE JAVA SEA - Duto Nugroho; Bonar P Pasaribu; Vincent P. Siregar (Indonesian Fisheries Research Journal, 2008)
Several acoustic surveys were carried out during a period of 1992 to 1995 in the main flshing ground of the pelagic fishery in the Java Sea. The collaboration between Indonesia and French made up within the frame of Pelfish Project.